Increasing children's literature capacity through village library during the Covid-19 pandemic - Dian Yosi Arinawati; Nyka Dwi Febria (Community Empowerment, 2023)
Literacy is defined as the ability to read, write and a person's ability to see the world and store information. The library is an effort to support education by providing teaching resources, information and references. During the Covid-19 pandemic, it was reported that there was a decrease in visits to the library. Like libraries in other areas, Muda Bhakti library located in Ngablak Village, Srumbung District, Magelang Regency, Central Java has also reportedly experienced a decrease in visitors during the Covid-19 pandemic. It is necessary to make innovations and concrete programs that are in accordance with the situation and conditions of the local community, especially targeting children, considering children are easy targets to be educated in an interesting way. The purpose of this community service is to carry out a children's literacy movement through the reactivation of the Muda Bhakti library during the Covid-19 pandemic. There are five main programs carried out in this service, namely 1) socialization of health protocols at the Muda Bhakti library during the Covid-19 pandemic, 2) hand washing practices according to WHO standards, 3) group learning for children in the library, 4 ) competitions in the form of writing short stories and coloring, 5) donations and book processing. The methods used to run the program are lectures, demonstrations and practice. This activity was attended by children from kindergarten to elementary school with a total of 60 children. This community service expected that it will be able to increase the literacy capacity of children during the Covid-19 pandemic.